Moral Development of Grade VIII Students Through Akidah Akhlak Learning - Irham, Muhammad; Lubis, Aminuddin; Yamin, Muhammad; Wahyuni, Sri; Grahmayanuri, Novria (Program Pascasarjana Institut Agama Islam Darullughah Wadda'wah Bangil Pasuruan, 2024)
The of students’ morals in the context of Islamic education has become very important, particularly through the learning of Akidah Akhlak. The objective of this research is to analyze the impact of Akidah Akhlak teaching on students’ morals and to identify the supporting and inhibiting factors involved. The research method used is a qualitative approach with interviews and observations involving 32 grade VIII students and their Akidah Akhlak teacher. The results indicate that students generally demonstrate good morals towards Allah SWT, their parents, and teachers, as evidenced by positive actions such as praying and showing respect. However, negative behaviors such as bullying and a lack of personal discipline still occur, highlighting the need for intervention through moral education, particularly through Akidah Akhlak learning. This study contributes important insights into the effectiveness of Akidah Akhlak education and aims to enhance teaching strategies and collaboration among teachers, students, and parents in fostering morally responsible individuals.